2021
DOI: 10.1017/s0022215121002279
|View full text |Cite
|
Sign up to set email alerts
|

Impact of olfactory dysfunction on quality of life in coronavirus disease 2019 patients: a systematic review

Abstract: Objective To outline the impact on quality of life in coronavirus disease 2019 patients with olfactory dysfunction. Methods Five databases were searched for articles referring to the impact on quality of life in coronavirus disease 2019 patients with olfactory dysfunction. The search was conducted for the period from November 2019 to April 2021. The search was conducted over one month (May 2021). Results Four studies that met the objective were included. Altogether, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
0
22
0
Order By: Relevance
“…Few studies exist on the evolution and recovery of COVID‐19–related olfactory dysfunction (OD) in the long term. Due to the impact of OD on the quality of life of patients, 1 it is mandatory to better define its characteristics, clinical course, and recovery times to properly counsel patients during medical visits as well as to conceive new therapeutic strategies to address the problem. The aim of this study was to describe the recovery pattern of OD in a cohort of COVID‐19 patients with an 18‐month follow‐up and to analyze the possible variables associated with spontaneous early or late recovery.…”
Section: Tablementioning
confidence: 99%
“…Few studies exist on the evolution and recovery of COVID‐19–related olfactory dysfunction (OD) in the long term. Due to the impact of OD on the quality of life of patients, 1 it is mandatory to better define its characteristics, clinical course, and recovery times to properly counsel patients during medical visits as well as to conceive new therapeutic strategies to address the problem. The aim of this study was to describe the recovery pattern of OD in a cohort of COVID‐19 patients with an 18‐month follow‐up and to analyze the possible variables associated with spontaneous early or late recovery.…”
Section: Tablementioning
confidence: 99%
“…A recent review of the literature [28] looking for studies on the impact of CD on QoL in COVID-19 found only four studies published so far [29][30][31][32]. These studies share some limitations which call into question the robustness of the conclusions made.…”
Section: Introductionmentioning
confidence: 99%
“…At least 40% of COVID-19 patients reported anosmia as an early sign of the disease, and nearly 70% of patients with OD claimed a reduced quality of life due to smell loss [13,22]. More than 10% of the infected with COVID-19 may suffer prolonged anosmia, often more than one year from the onset of the disease [17,23].…”
Section: Olfactory Dysfunctions Associated With Covid-19mentioning
confidence: 99%